Exploring de-facto accountability regimes in Muslim NGOs. Issue 3 (September 2018) - Yasmin, Sofia; Ghafran, Chaudhry; Haniffa, Roszaini
Abstract: This paper aims to deepen and advance our understanding of the de-facto accountability processes and practices within Muslim non-governmental organisations (NGOs). We employ a three-fold accountability framework of felt, imposed and adaptive accountability, supported by insight from the Islamic perspective to elucidate our empirical findings. We adopt this framework because it enables us to localise the notions of accountability, allowing a more complete understanding of the de-facto nature of Muslim NGO accountability to emerge within the context of religious ideals and between accountabilities that are externally imposed and those that are internally generated.